Uniformity in the application of the CISG analysis of the problem and recommendations for the future - Prastalo, Boris (Global trade law series ;, 2020)
"Uniformity in the Application of the CISG' offers a detailed examination of the principle of uniformity as enshrined in Article 7(1) of the United Nations Convention on Contracts for the International Sale of Goods (CISG). More than ninety countries are now parties to the CISG - recognised as the pre-eminent legislative achievement aimed at harmonising commercial law on a global scale - but uniformity in the treaty's application remains unsettled and controversial. This book aids in a complete understanding of the CISG interpretative methodology and its different components and draws on issues raised over thirty years of case law across the world and from other CISG-related materials to clearly delineate a path to more uniform application"--